(untitled) (Edad Media. Revista de Historia, 2025)
In this essay we try to prove the great importance of jihad for the Banū Naṣr dynasty (al-Andalus, 1232-1492) and its commitment to the observance of the Islamic precept for the political and institutional stability of the Nasrid Emirate. Relying on a wide selection of Arabic sources from the Nasrid period, we offer a new perspective on the high involvement in warfare on the part of the Nasrid sultans, in contrast to the conjectures that pointed to the disinterest or lack of effort of the Andalusians in the jihad in previous stages. We present a diachronic analysis that deals with the jihad of most of the emirs of Granada, observing both the idealized image in inscriptions and the military activity that was recorded in chronicles or diplomatic correspondence. Consequently, we reach the conclusion that the jihad of the Banū Naṣr -both their discourse and practice- constituted a fundamental pillar of the Nasrid Emirate.